Revisiting the role of education for agricultural productivity - Malte Reimers; Stephan Klasen (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2011)
While the majority of micro studies finds that rural education increases agricultural productivity, various recent cross-country regressions analyzing the determinants of agricultural productivity were only able to detect an insignificant or even surprisingly negative effect of schooling. In this paper, we show that this failure to find a positive impact of education in the international context appears to be a data problem related to the inappropriate use of enrolment and literacy indicators. Using a panel of 95 developing and middle-income countries from 1961 to 2002 that includes data on educational attainment, we show that education indeed has a highly significant, positive effect on agricultural productivity which is robust to the use of different control variables, databases and econometric methods. Distinguishing between different levels of education further reveals that only primary and secondary schooling attainment has a significant positive impact while the effect of tertiary education is insignificant. When distinguishing between income groups, our results indicate that even though the coefficient of the education variable is highly significant and positive for all quintiles, the returns to education are higher for the countries belonging to the richest three quintiles. This finding can be interpreted as support for the claim that education will have larger impacts on agricultural productivity in the presence of rapid technical change since it helps farmers to adjust more readily to the new opportunities provided by technological innovations.
Keywords: I20; I25; O13; O15; O47; Q10; 330; agricultural productivity; agricultural production function; cross-country regression; education; human capital; Bildungsniveau; Agrarproduktion; Landwirtschaft; Produktivität; Schätzung; Entwicklungsländer; Schwellenländer